Impact of Digital Marketing on Market Expansion and Development in MSMEs - Yulia Amanda; Aidil Akbar; Ridho Awali (Yayasan Bayt Shufiya Nusantara, 2025)
The development of digital technology has significantly transformed marketing practices, shifting from traditional strategies to more modern, online-based approaches that offer speed, efficiency, and measurable performance. For Micro, Small, and Medium Enterprises (MSMEs), digital marketing has become an essential tool to broaden market reach, enhance brand awareness, and strengthen competitiveness in an increasingly saturated and dynamic business environment. This study aims to explore the influence of digital marketing on market development among MSMEs by examining aspects such as customer reach, promotional effectiveness, engagement levels, and sales growth. A qualitative descriptive method is applied through in-depth interviews, supported by literature review and secondary data related to MSME development and current digital marketing trends. The findings show that digital marketing provides substantial benefits for MSMEs by improving business visibility, facilitating real-time interaction with consumers, increasing cost-effectiveness, and enabling access to wider, including international, markets. However, the level of success strongly depends on the ability of MSME actors to consistently manage digital platforms, create relevant high-quality content, and understand algorithm dynamics and consumer behavior patterns.